1973
DOI: 10.2307/1935670
|View full text |Cite
|
Sign up to set email alerts
|

Natural Mortality of Tadpoles in a Population of Rana Aurora

Abstract: The Survivorship, distribution, growth rates, and natural predation rates on the population of Rana aurora tadpoles in Marion Lake, British Columbia, were studied during the summers of 1969 and 1970. Natural survivorship appeared to have two phases: a rapid decline in numbers during the first 4 weeks after hatching was followed by a less rapid decline, until approximately 5% of the population remained at metamorphosis, after 11—14 weeks. The size attained by tadpoles living at any depth in the lake was strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1
2

Year Published

1980
1980
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(119 citation statements)
references
References 14 publications
(21 reference statements)
6
110
1
2
Order By: Relevance
“…He found that survivorship had two phases; a rapid decline in numbers during the first 4 weeks after hatching followed by a less rapid decline, until about 5 percent of the population remained at metamorphosis, after about 11 to 14 weeks. Mortality was density-dependent, and predation was the major cause of mortality in Calef's (1973b) study.…”
Section: Ecology and Behaviormentioning
confidence: 82%
See 1 more Smart Citation
“…He found that survivorship had two phases; a rapid decline in numbers during the first 4 weeks after hatching followed by a less rapid decline, until about 5 percent of the population remained at metamorphosis, after about 11 to 14 weeks. Mortality was density-dependent, and predation was the major cause of mortality in Calef's (1973b) study.…”
Section: Ecology and Behaviormentioning
confidence: 82%
“…Young larvae are tolerant of temperatures between 4 and 21 °C (Licht 1971, Nussbaum andothers 1983). Calef (1973b) studied the natural mortality of R. aurora tadpoles in a lake in British Columbia. He found that survivorship had two phases; a rapid decline in numbers during the first 4 weeks after hatching followed by a less rapid decline, until about 5 percent of the population remained at metamorphosis, after about 11 to 14 weeks.…”
Section: Ecology and Behaviormentioning
confidence: 99%
“…Since that study numerous articles have shown substantial premetamorphic mortality which may affect the numbers and kinds of individuals recruited into the adult population. The important mortality factors shown or suggested are numerous and include temperature, ephemeral habitats, rainfall, disease, predation, competition, and chemical effects (Martof, 1956;Turner, 1960Turner, , 1962Herreid and Kinney, 1966;Worthington, 1968;Brockelman, 1969;Anderson et al, 1971;Wilbur, 1971Wilbur, , 1972Calef, 1973;DeBenedictis, 1974;Shoop, 1974;Collins, 1975;Heyer et al, 1975;Heyer, 1976;Pough, 1976;Woodruff, 1976;Howard, 1978;Smith-Gill and Gill, 1978). In all of these studies (except Howard, 1978) embryos or larvae of a population are treated as a homogeneous group with potential mortality factors affecting each individual with equal probability.…”
Section: Resultsmentioning
confidence: 99%
“…Mortality rates of foam nesting frogs are considered moderate compared to other anuran species. For example, the mortality rates reported for several pond breeding species vary from 0.024-0.426 [31][32][33][34]. The values reported range between 0.5-0.6 for a tropical hylid species [35].…”
Section: Discussionmentioning
confidence: 99%